Five-year trends in psychiatric inpatient care: insights from 5,887 patients on substance use, involuntary admissions, and treatment approaches - Akdag, Emine Merve; Civan Kahve, Aybeniz; Ay Diker, Rukiye; Aydın, Serap; Arslan Barlas, Zeynep; Aktürk, Tuğba (Frontiers in Psychiatry, 2026)
ObjectiveThis study aimed to examine the prevalence and temporal trends of SUDs among psychiatric inpatients, investigate the factors predicting involuntary hospitalization, and assess the impact of SUDs and involuntary admission on pharmacological treatment practices.MethodsA retrospective cross-sectional analysis was conducted using medical records of all psychiatric inpatients (n = 5,887) admitted to the general psychiatric wards of a regional training and research hospital between 2019 and 2023. Descriptive statistics, logistic regression, linear regression, and seemingly unrelated regression (SUR) analyses were employed to evaluate clinical predictors and treatment trends.ResultsThe prevalence of SUD was 27.5% (n = 1,619), with mixed substance use being the most common pattern (76.1%). In the logistic regression model, substance use, male sex, and later years of admission were associated with a higher likelihood of involuntary hospitalization, whereas bipolar affective disorder was associated with a lower likelihood. Treatment trends showed an overall increase in atypical antipsychotics, depot antipsychotics, clozapine, and electroconvulsive therapy (ECT); compared with non-users, patients with SUD showed lower use of typical antipsychotics, mood stabilizers, clozapine, and ECT.ConclusionsThis large-scale study demonstrates that SUDs are a strong predictor of involuntary psychiatric hospitalization and significantly influence pharmacological treatment patterns. The increasing trend of compulsory admissions, particularly among male patients with SUD, underscores the urgent need for clearer legal and ethical frameworks, as well as the expansion of community-based mental health services in Türkiye.